Representaciones sociales sobre el reclutamiento a grupos armados ilegales que tienen los jóvenes residentes en el resguardo indígena de Toribio Cauca. (2023)
The purpose of this research is to analyze the social representations that young people residing in the indigenous reservation of Toribio Cauca have regarding recruitment to illegal armed groups. The interest of this research arises from the experiences and news of the armed conflict that occurred in the Municipality of Toribio, and the way in which it has been faced by those who have been affected by the loss of their loved ones, friends, neighbors and family.